EKSISTENSI SALAWEK DULANG PADA MASYARAKAT PADANG SIBUSUK KECAMATAN KUPITAN KABUPATEN SIJUNJUNG - Indah Mardiani; Tulus Handra Kadir; Irdhan Epria Darma Putra (SENDRATASIK UNP, 2018)
Abstract This article aims to find out and describe the existence of Selawat Dulang in Padang Sibusuk community which includes the use, function, position, meaning and effort to keep the existence of Selawat Dulang in Nagari Padang Sibusuk. This research was descriptive research using a qualitative approach. Instruments in this study were researcher self and assisted with the supporting instruments such as notebooks, stationery, and camera. The technique of data collection was done through literature study, observation and interview. The technique of data analysis was done by observation steps, identifying data, interpreting data, describing data and making discussion. The results show that the Art of Selawat Dulang is still existing and awakened in the mind of Padang Sibusuk people in accordance with the needs of Padang Sibusuk community. This study shows that Selawat Dulang has several functions. They are social function, as entertainment and group existence. The results prove that the position and meaning of Selawat Dulang in the community of Padang Sibusuk strengthening its existence and making Selawat Dulang as a form of cultural preservation. Keywords: Use, Function, Meaning, Existence, Selawat Dulang